The Last Lick: A Lived Experience of Non-incarcerated Partners - Adetunji, Christian Matthew; Wambugu, Anne Gathoni; Kamau, Elizabeh Wangui (European Scientific Journal, ESJ, 2023)
The incarceration of their partners has a profound effect on the non-incarcerated ones. But what are these effects, and what are the results? The purpose of this study was to (1) assess the notable feelings experienced by non-incarcerated partners and (2) understand the implications of these feelings. Semi-structured interviews were conducted with 10 female participants who had their partners incarcerated at Nigeria’s Agodi-Ibadan Medium Correctional Facility. An interpretative phenomenological approach was employed to analyse their lived experience with Satir’s model. Thirteen sub-themes derived from feelings revealed the participants’ frustration, pain, and hurt; betrayal and anxiety; anger, confusion, and interruption; hostility, hunt, and fear; sadness, shame, and humiliation; being depressed and incarcerated; being surprised and in denial; being confused and helpless; being sorry and suffering double losses; being controlled as well as feeling relieved. This study found that 40% of participants felt frustrated, angry, interrupted, and hunted, while 30% felt hurt, bitter, or humiliated, and 20% felt betrayed, incarcerated, in denial, confused, or had a sense of relief while their partners were incarcerated. These experiences intensified the impacts of their partners’ incarceration. The study has recommendations for marriage and family specialists.